Clinico-Epidemiological Scenario, Laboratory Evaluation and Admitted Geriatric COVID-19 Patients in Bangladesh - Biswas, Sarmistha; Begum, Ayesha; Uddin, Md. Nasir; Rashid, Mamun ur; Hawari, Najir; Mia, Md. Titu (Cardiology and Cardiovascular Medicine, 2024)
Introduction: Coronavirus disease (Covid-19) is an infectious disease caused by the SARS-CoV-2 virus. Covid-19 can be austere and has caused billions of demise. Covid-19 causes higher mortality proportions in elderly patients along with other health complications such as cardiovascular disease, chronic respiratory system diseases, hypertension, diabetes and malignant diseases Aim of the study: The study aimed to identify the clinico-epidemiological scenario, laboratory evaluation, and outcome of admitted geriatric Covid-19 patients in Bangladesh. Methods: The study was conducted in three dedicated COVID-19 treatment centres in Dhaka city throughout July in the year 2021. Three facilities were Dhaka Medical College Hospital-2 (DMCH-2, COVID-19 dedicated 600 beds), Dhaka North City Corporation Hospital (DNCC, COVID-19 dedicated 750 beds), and Kuwait Moitry Hospital (COVID-19 dedicated 240 beds). A total of three forty-five (N=345) geriatric patients fulfilling the inclusion criteria were enrolled in the study. Verbal consent was attained from every subject or guardian of the patient. The data analysis was performed using Statistical Package for the Social Sciences (SPSS) Version 25.0. Result: The majority of the present study participants (84.06%) were between the age group of 61-70 years, while 13.04% were between the age of 71-80 years A little higher female prevalence was observed. For the diagnosis of COVID, RT-PCR was used for 87.83% of the participants, 7.25% had been diagnosed via RAT, and 4.93% were suspected COVID cases. Among the presenting complications of the participants, the cough had the highest prevalence at 88.99%. Among the 345 patients, 40% had abnormal oxygen saturation levels, 89% had abnormal WBC counts, 66.1% had abnormal neutrophil counts, 82.9% had abnormal lymphocyte counts, 6.1% had hypoglycemia, 25.2% had hyperglycemia, 29.0% had abnormal creatinine levels, 13.3% had abnormal SGPT levels, and 4.3% had abnormal serum D-Dimer levels. Serum ferritin level was abnormal in 89.3% of the male population and 80.10% of the female population. Conclusion: Initial detection of SARS-CoV-2 infected individuals is vital to contain the extent of the Covid-19 pandemic and efficiently allocate medical resources. Elderly patients with COVID-19 need more medical maintenance. Approaches should be needed for sensible use of hospital assets during the pandemic surge to alleviate the number of death.